2022
DOI: 10.1111/tpj.15984
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of isoform‐level gene expression patterns across tissues during lotus species divergence

Abstract: Both gene duplication and alternative splicing (AS) drive the functional diversity of gene products in plants, yet the relative contributions of the two key mechanisms to the evolution of gene function are largely unclear.Here, we studied AS in two closely related lotus plants, Nelumbo lutea and Nelumbo nucifera, and the outgroup Arabidopsis thaliana, for both single-copy and duplicated genes. We show that most splicing events evolved rapidly between orthologs and that the origin of lineage-specific splice var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…A previous study revealed that the expression patterns of genes in lotus were different in multiple tissues [ 32 ], which enabled further investigation of the tissue expression level of the NnWOX genes. Interestingly, we only found similar tissue expression patterns between the duplicated NnWOX13a/b genes in the ancient clade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study revealed that the expression patterns of genes in lotus were different in multiple tissues [ 32 ], which enabled further investigation of the tissue expression level of the NnWOX genes. Interestingly, we only found similar tissue expression patterns between the duplicated NnWOX13a/b genes in the ancient clade.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the minimum sample size and correlation of gene modules and tissue, weight gene co-expression network analysis (WGCNA) was widely used for identifying the co-expressed gene pairs in different plant tissues or experimental treatment samples [ 59 , 60 , 61 ]. Previous transcriptomic research on lotus has constructed a gene-level network involved in only six tissues and a transcript-level co-expression network including eleven tissues using WGCNA [ 32 , 62 ]. In this study, we used the same pipeline of WGCNA to construct the gene co-expression networks for each NnWOX gene ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation